2012
DOI: 10.5001/omj.2012.114
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and Non-Obstetric Risk Factors for Cesarean Section in Oman

Abstract: The study calls for increasing awareness about clinical and public health majors that would lead to prevention of risk factors associated with increased risk of cesarean section such as maintaining normal BMI and prevention of gestational and type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
28
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 25 publications
15
28
2
2
Order By: Relevance
“…Majority (72.3%) of mothers gestational age at labor was less than 38 weeks, but in study done in Oman the majority of the mothers gestational age is above 38 weeks [14]. in this study, maternal age is significantly associated with cesarean section in line with other different studies [14,15]. Being undergone cesarean section more likely increase as age of mothers increase.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Majority (72.3%) of mothers gestational age at labor was less than 38 weeks, but in study done in Oman the majority of the mothers gestational age is above 38 weeks [14]. in this study, maternal age is significantly associated with cesarean section in line with other different studies [14,15]. Being undergone cesarean section more likely increase as age of mothers increase.…”
Section: Discussionsupporting
confidence: 85%
“…But it is lower as compared with the study done in Brazil which is 94.7% [6]. Majority (72.3%) of mothers gestational age at labor was less than 38 weeks, but in study done in Oman the majority of the mothers gestational age is above 38 weeks [14]. in this study, maternal age is significantly associated with cesarean section in line with other different studies [14,15].…”
Section: Discussionsupporting
confidence: 80%
“…Our caesarean section rate is above the established fork of the World Health Organization. 16 On another hand, ptresent rate is much lower than the rate of 40.1% found in study in Lagos-Nigeria and 43% rate from public hospitals in Brazil. 17,18 Present high caesarean section rate is due to high rate of emergency sections (85.0%), where referral cases are managed from 5 districts and their peripheries as it is the only tertiary care facility in South Kivu Health Division.…”
Section: Discussioncontrasting
confidence: 41%
“…Other studies on the same subject showed that advanced maternal age remain a leading factor associated with caesarean section. 16,1920 This can be explained by the fact that older women are more likely to experience pregnancy complications such as diabetes, hypertension and pre-eclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…9 In Oman, the CS rate gradually increased from 9.7% in 2000 to 15.7% in 2009. 10,11 At the Sultan Qaboos University Hospital (SQUH), a tertiary care university hospital in Muscat, Oman, the annual delivery rate was approximately 3,800 in 2013, with a CS rate of 18%.…”
mentioning
confidence: 99%